Old melioration systems: the influence onto functioning of geoecosystems of river valleys in the Parsęta basin (NW Poland) - Szpikowski, Józef; Szpikowska, Grażyna; Domańska, Monika (Wydział Nauk Geograficznych i Geologicznych Uniwersytetu im. Adama Mickiewicza, 2015)
Meliorations and their specific forms – irrigations – are one of the forms of anthropopressure within geoecosystems. The research studies conducted within the Parsęta basin focused on the sub-irrigation (seepage irrigation) systems formed in the 19th century. Query of archive materials and maps, hydrochemical and phytosociological terrain mapping and laboratory testing of water samples collected were used in the studies. In the study area were found the remains of the thirty old irrigation systems, which together occupy 2% of the Parsęta basin area. For many years most of them have not fulfilled their primary economic functions. Still, these systems have an impact on the cycle of waters and have become an important factor in increasing the geo- and biodiversity within the postglacial landscape. By expanding a range of wetland riparian areas, they fulfil relevant functions to protect surface waters against the supply of biogenic components. Some of them could be used to enlarge wetlands and floodplains within river valleys.
Keywords: meliorations; irrigations; West Pomerania; the Parsęta basin; geoecosystems of river valleys; geo- and biodiversity